Reading comprehensión among college students - Peñafiel Arcos, Edison Boanerges (SATHIRI, 2018)
The understanding of a text should be interpreted at different levels: literal, inferential and critical-evaluative. A literal level is to understand everything that the author explicitly com- municates through a text; understanding a text at an inferential level means to interpret everything that the author wants to communicate, but that sometimes he does not explicitly say or write; understanding a text at a critical- evaluative level means to value, project and judge both the content of what one author states in his writing as well as the inferences or relationships that can be established from what appears in the text produced by an author. Some researches consider that college student graduates are not necessarily good readers even though they read advanced academic material, for this reason they do not always com- prehend the information. Many strategies have been proposed to be developed both in class and at home, to improve reading comprehension. Instructors can improve comprehension through non-reading related information such as background knowledge or experiences, ho- mework and class work, and learning aides. Instructors can also teach students how to use other strategies including the SQ3R method, peer teaching, encoding, and reading flexibility.